Extending the applicability of the super-Halley-like method using ω-continuous derivatives and restricted convergence domains - Argyros, Joannis K.; George, Santhosh (Annales Mathematicae Silesianae, 2018)
We present a local convergence analysis of the super-Halley-like method in order to approximate a locally unique solution of an equation in a Banach space setting. The convergence analysis in earlier studies was based on hypotheses reaching up to the third derivative of the operator. In the present study we expand the applicability of the super-Halley-like method by using hypotheses up to the second derivative. We also provide: a computable error on the distances involved and a uniqueness result based on Lipschitz constants. Numerical examples are also presented in this study.